Molecular mechanisms of aroma persistence: From noncovalent interactions between aroma compounds and the oral mucosa to metabolization of aroma compounds by saliva and oral cells. (30th March 2022) - Muñoz-González, Carolina; Brule, Marine; Martin, Christophe; Feron, Gilles; Canon, Francis
Highlights: Aroma compounds are able to interact with the mucosal pellicle ex vivo. Oral cells and saliva metabolize specific aroma compounds ex vivo. Aroma compounds metabolized by oral cells and saliva show low persistence in vivo. Human physiology is a key parameter in the aroma persistence phenomenon. Abstract: The present study aims to reveal the molecular mechanisms underlying aroma persistence, as it plays a major role in food appreciation and quality. A multidisciplinary approach including ex vivo experiments using a novel model of oral mucosa and saliva as well as in vivo dynamic instrumental and sensory experiments was applied. Ex vivo results showed a reduction in aroma release between 7 and 86% in the presence of the thin layer of salivary proteins covering the oral mucosa (mucosal pellicle). This reduction was explained by hydrophobic interactions involving the mucosal pellicle and by the ability of oral cells and saliva to metabolize specific aroma compounds. The in vivo evaluation of exhaled air and perception confirmed the ex vivo findings. In conclusion, this work reveals the need to consider physiological reactions occurring during food oral processing to better understand aroma persistence and open new avenues of research.